Superconducting gap of H3S measured by tunnelling spectroscopy - Feng Du; Alexander P. Drozdov; Vasily S. Minkov; Fedor F. Balakirev; Panpan Kong; G. Alexander Smith; Jiafeng Yan; Bin Shen; Philipp Gegenwart; Mikhail I. Eremets (Nature, 2025)
Abstract Several hydrogen-rich superconductors have been found to show unprecedentedly high critical temperatures1–4, stimulating investigations into the nature of the superconductivity in these materials. Although their macroscopic superconducting properties are established1,5–7, microscopic insights into the pairing mechanism remains unclear. Here we characterize the superconducting gap structure in the high-temperature superconductor H3S and its deuterium counterpart D3S by performing tunnelling spectroscopy measurements. The tunnelling spectra reveal that H3S and D3S both have a fully gapped structure, which could be well described by a single s-wave Dynes model, with gap values 2Δ of approximately 60 meV and 44 meV, respectively. Furthermore, we observed gap features of another likely H-depleted H x S superconducting phase in a poorly synthesized hydrogen sulfide sample. Our work offers direct experimental evidence for superconductivity in the hydrogen-rich superconductor H3S from a microscopic perspective. It validates the phonon-mediated mechanism of superconducting pairing and provides a foundation for further understanding the origins of high-temperature superconductivity in hydrogen-rich compounds.